Social ecology - Guha, Ramachandra (Oxford in India readings in sociology and social anthropology., 1994)
Oxford in India Readings in Sociology and Social Anthropology have been carefully planned to suit the needs of the general reader, students, teachers, as well as scholars from other disciplines. Problems have been posed in general theoretical terms, but Indian ethnography has been used as far as possible to illustrate them. Each volume is devoted to a core area in sociology and social anthropology and brings within one cover important writings, some of which are very difficult to obtain.